A novel capsular operon and potentially conjugative plasmids in extensively drug-resistant urogenital Haemophilus parainfluenzae - Saiz-Escobedo, Lucía; Ballestero-Tellez, Mónica; Rajadell, Mireia; Garreta-Esteban, Marc; Gisbert, Laura; Cadenas-Jiménez, Irene; Costa, Rosa Maria; Tubau, Fe; Sánchez-Ramos, David; Domínguez, M. Angeles; Xanthopoulou, Kyriaki; Higgins, Paul G.; et al. (Frontiers in Microbiology, 2025)
IntroductionHaemophilus parainfluenzae is an opportunistic pathogen increasingly associated with urogenital infections and multidrug resistance. While polysaccharide capsules are known virulence factors in H. influenzae, their role in H. parainfluenzae remains poorly understood. This study aimed to characterize a new capsular operon identified in H. parainfluenzae and analyze the antimicrobial resistance profile of strains carrying this operon to provide insights into their pathogenic potential.MethodsTwo clinical isolates from genital ulcers were subjected to whole-genome sequencing. The capsular operon was identified and characterized using comparative genomics. Antimicrobial susceptibility was determined using broth microdilution, and the resistance determinants were identified through genomic analysis.ResultsA novel capsular operon, designated H. parainfluenzae HPAR_type4, was identified in both isolates. This operon spans 11,885 bp and comprises nine predicted open reading frames (ORFs) organized into the three regions characteristic of Haemophilus spp. Regions I, III, and the first ORF of region II showed high homology with the HPAR_type1 operon, while the remaining ORFs in region II shared identity with the cpsB and cpsC genes from H. sputorum HSPU_type1. Both strains exhibited multidrug resistance, with one strain carrying a CTX-M-15 extended-spectrum β-lactamase gene integrated in an integrative and conjugative element (ICE), ICEHpaHUB6. Two distinct potentially conjugative plasmids were identified, each carrying genes related to replication, mobility, and putative virulence functions.ConclusionThe identification of a novel capsular operon in multidrug-resistant H. parainfluenzae strains highlights the species genetic plasticity and potential for increased virulence. These findings underscore the importance of ongoing surveillance in clinical settings to monitor the spread of antibiotic resistance and novel virulence factors, which may contribute to its pathogenicity and impact future treatment strategies.